TYPOLOGICAL ANALYSIS OF THE ROAD TRANSPORT SYSTEM AND URBAN SPATIAL ORGANISATION USING CADMAPPER AND OPENSTREETMAP (OSM). CASE STUDY: BISTRIȚA-BECLEAN-NĂSĂUD-SÂNGEORZ-BĂI URBAN AXIS - TĂTAR, Alexandru Marius; POP, Călin Cornel; BÎCA, Ioan (Studia Universitatis Babeș-Bolyai Geographia, 2025)
This research presents an analysis of typological aspects of the road stacking system and their impact on the spatial organisation of urban functions along the Bistrița–Beclean–Năsăud–Sângeorz-Băi urban axis, following the structure and definitions of the analytical study in The Role of Streetscape (Tătar, A.M., Pop, C.C., 2025). The study emphasises how types of roads create organisational structures and affect the distribution of commercial, economic, tourist, and cultural locations, as well as the functioning of urban industries in a medium-sized urban area. The study used Cadmapper and OpenStreetMap (OSM), which are freely accessible geospatial datasets, to assign types of roads and map the spatial logic and configuration of urban functions. By employing typological mapping and spatial analysis, this research identified various transport types and functional types, as well as their relationships. In doing so, this enables the role of urban land utilisation. The results revealed how road slab structures and hierarchies affected the location of urban functions differently. While specific types of roads produced the most effective spatial organisation in transport models, certain kinds of roads influenced urban structure and efficiency less than others. The study highlights the significance of transport system typology in urban planning as a crucial element of sustainable development and functional zoning. The paper provides the basis for developing better urban diagnostics and urban contrasts, as well as strategies that take into consideration development scenarios specific to Bistrița-Năsăud area.